Educational Challenges of People with Albinism - Adhikari, Khagendra Prasad (Karnali Outlook: Knowledge Across Disciplines, 2026)
Educational challenges of People with Albinism in Karnali Province, Nepal. This study explores the educational challenges of people with albinism in Karnali Province, Nepal, with a focus on their educational challenges, and recommendations for improving accessibility and infrastructure in education. The research adopts a mixed research method, combining quantitative and qualitative data collection techniques. A structured questionnaire was administered to all 39 identified individuals with albinism in the study area, while in-depth interviews and key informant discussions provided qualitative insights into their experiences and systemic barriers. Observations of schools and community settings complemented these methods, allowing for a comprehensive analysis of the educational environment for people with albinism and snowball sampling was used to find out the respondents through a network of people with albinism in Karnali province. The findings reveal significant barriers to education for people with albinism, including inadequate infrastructure, social stigma, and limited access to assistive tools. Recommendations include enhancing educational infrastructure, providing specialized learning materials, and implementing awareness programs to address societal misconceptions. By identifying these challenges and proposing solutions, the study contributes to the broader discourse on inclusive education and social equity for marginalized communities in Nepal.